Xylaria species associated with fallen fruits and seeds. (4th July 2018) - Ju, Yu-Ming; Rogers, Jack D.; Hsieh, Huei-Mei
ABSTRACT: Twenty-five fructicolous and seminicolous species of Xylaria are classified into three groups by stromatal morphology: (i) the X. ianthinovelutina group; (ii) the X. carpophila group; and (iii) the X. heloidea group. Xylaria reevesiae, X. rossmanae, and X. vivantii are described as new species. Xylaria reevesiae belongs to the X. carpophila group, resembling X. euphorbiicola but differing from it mainly by having conspicuous perithecial mounds and growing on fallen fruits of a different host plant. Xylaria rossmanae and X. vivantii belong to the X. ianthinovelutina group. Xylaria rossmanae differs from the species of the group mainly by larger, paler, fusoid-inequilateral ascospores, and X. vivantii differs by larger ascospores with a slightly oblique germ slit. A dichotomous key is provided for identifying the 25 species. Doubtful names are also listed and annotated.